REPLACEMENT OF ‘DELICIOUS’ EXPRESSION: DENOTATIVE-CONNOTATIVE MEANING ANALYSIS - Ayunda Rizky Nur Rohmah; Nur Latifah (Journal of Language and Literature, 2022)
The study of meaning concerns the two branches of oral and written communication systems. Through the study of denotative and connotative meanings to understand someone's utterances. This study aims to provide a broader understanding of the urgency of modification. According to narration through understanding connotative and denotative meanings. This study uses a qualitative descriptive system. Implicitly, denotative-connotative substances give rise to purposes that are not always the same. Although they are types of the same word or referred to by a similarity, they have different meanings. This difference in meaning can then be translated based on connotative and denotative meanings through the three videos used in the research. In datum one, what found it was found to use positive connotative meaning eight times, negative connotative meaning six times, and denotative meaning four times. In datum number two, ten words with positive connotations were found, and three denotative substances were used, but no negative connotations were found in the second datum. In the third datum, there are fifteen positive connotative meanings and two denotative usage words.